Paget’s Disease of Bone and Calcium Homeostasis: Focus on Bisphosphonate Treatment - Polyzos, S. A.; Anastasilakis, A. D.; Makras, P.; Terpos, E. (Experimental and Clinical Endocrinology & Diabetes, 2011)
Paget’s disease of bone (PDB) is the second most common metabolic bone disease. Bisphosphonates (BPs) are currently the drugs of choice for PDB. PDB and osteomalacia are both common in the elderly. The concept of relative vitamin D deficiency in patients with PDB was suggested long ago, but it has not yet elucidated. Both diseases predispose to fractures, but their combined action to fragility has not been studied yet. The older BPs, mainly etidronate, further inhibit bone mineralization. Mineralization defects have also been described in patients with PDB treated with pamidronate. Moreover, hypocalcemia and secondary hyperparathyroidism after treatment with BPs have been described in PDB. Hypocalcemia seems to be more severe after treatment with the more potent, intravenous zoledronic acid, which is currently the treatment of choice for PDB. The counteracting hyperparathyroidism pathophysiologically intends to increase renal reabsorption of calcium and 1.25-dihydroxy vitamin D production and to stimulate osteoclasts in order to prevent long-term hypocalcemia. However, the effect of PTH on osteoclasts is, at least partly, restricted in patients taking BPs. Secondary hyperparathyroidism is a potentially detrimental condition, especially in patients already suffering from another bone disease. Serum calcium and vitamin D deficiency should be restored before BP treatment and calcium and vitamin D administration should be possibly continued for longer after achieving normocalcemia, which may shorten the duration of secondary hyperparathyroidism.Mineralization defects and hypocalcemia with secondary hyperparathyroidism have been described in patients with Paget’s disease of bone treated with bisphosphonates. Secondary hyperparathyroidism may be a potentially detrimental condition for patients with Paget’s disease of bone.
Keywords: bisphosphonate; hyperparathyroidism; hypocalcemia; Paget’s disease; vitamin D